Local circuits and ocular dominance columns in monkey striate cortex - Katz, LC (J Neurosci, 1989)
The relationships between ocular dominance columns and intrinsic cortical circuitry were examined in brain slices prepared from the striate cortex of macaques. Ocular dominance columns in layer 4C beta were visualized in vitro following anterograde transport of rhodamine injected into the lateral geniculate nucleus in vivo. The axonal and dendritic arborizations of individual layer 4C beta cells were revealed by intracellular fluorescent dye injections. Both qualitative observations and quantitative analysis showed that the dendrites of cells close to borders remained preferentially, although not absolutely, in the “home” column (the column containing the cell body). Thus, the segregated pattern of afferent input appears to have considerable influence on the pattern of dendritic arbors. Similarly, while axon collaterals within layer 4C beta could cross into the adjacent column, their limited lateral spread produced arbors that remained primarily within the home column. The terminal arbors of collaterals that travelled from layer 4C beta to layer 3 had a larger lateral spread, and the termination pattern appeared to be independent of column borders. Thus, our observations indicate that, while the course of many layer 4C beta dendrites appears to be guided by columnar boundaries as defined by geniculate afferents, there exist morphological substrates for intercolumnar interactions even between 4C beta cells. Intercolumnar interactions are seen more commonly in layer 3, however, where larger, denser axon arbors originating from 4C beta cells can freely cross ocular dominance column boundaries.